Processing trade and global supply chains: Towards a resilient "GVC 2.0" approach - Lucian Cernat (European Centre for International Political Economy (ECIPE), 2022)
In the current global context marked by economic fragility, growing uncertainty and geopolitical conflicts, ensuring the smooth functioning of global supply chains becomes more important than ever. Supply shortages, higher freight costs, higher commodity prices and strong demand increase will trigger inflationary pressures for all economic sectors dependent on global value chains (GVCs). As part of global efforts to enhance the resilience of GVCs, this paper makes the case for a broader discussion about the untapped potential of processing trade, a relatively unknown trade facilitation option available in many countries around the world. Processing trade has been credited with stimulating China's participation in GVCs, in combination with foreign direct investment (FDI) attraction and industrial upgrading. However, processing trade is not just a Chinese phenomenon. In the EU, significant trade flows (over 200 billion euros in 2021 alone) benefitted from a double-digit trade cost reduction, thanks to the EU processing trade provisions. Different types of processing trade arrangements exist in over 70 countries worldwide (including in the EU), as a way to facilitate the integration of developing countries in global production chains. However, these unilateral schemes have different requirements and co-exist without any attempt to facilitate their inter-operability along complex global supply chains. This paper argues that there is a pressing need for a global reflection on how best to promote a better integration between these national processing trade schemes. One option is to promote a "GVC 2.0" approach that offers key recommendations and best practices for processing trade along GVCs. Such a coordinated "GVC 2.0" trade facilitation initiative would not only make GVCs more resilient for countries that depend on global sourcing for their critical economic activities, but it will also reduce the inflationary effect generated by the unnecessary trade costs associated with GVC activities.
Keywords: 330; Lieferkette; Globale Wertschöpfungskette; Importwirtschaft; Exportwirtschaft; Außenhandel; Welt; China